Body fat distribution: the answer to the apparent paradox of obesity in cardiology? - Daria A. Borodkina; Olga V. Gruzdeva; Ludmila V. Kvitkova; Olga L. Barbarash (Ожирение и метаболизм, 2017)
Today, despite all the measures taken, cardiovascular diseases remain the main cause of temporary invalidization, disability and mortality. Obesity is a major risk factor of cardiovascular diseases and complications from them. However, not all fat depots have the same proinflammatory, paracrine and metabolic activity. Recent studies have shown that the accumulation of visceral fat, and not subcutaneous fat, is associated with an increase in cardiometabolic risk. At the same time, there is evidence that an increase in the area of visceral fat is a protective mechanism against lipotoxicity. The purpose of this review is to discuss current literature data reflecting the characteristics of the visceral, epicardial and perivascular fat depots, and also their association with cardiovascular diseases.